Enhanced Antioxidant and Cytotoxic Potentials of Lipopolysaccharides-Injected Musca domestica Larvae - Islam El-Garawani; Hesham El-Seedi; Shaden Khalifa; Islam H. El Azab; Marwa Abouhendia; Shaymaa Mahmoud (MDPI AG, 2020)
The usage of insects as a sustainable and functional natural products resource is a new promise in complementary and alternative medicine. The present study aimed to investigate the ability of Musca domestica (housefly) larval hemolymph (insect blood) to display the enhanced in vitro antioxidant and cytotoxic effects. The oxidative stress (OS) was elicited by inducing lipopolysaccharides (LPS) treatment as an exogenous stressor. Determination of superoxide dismutase 1 (SOD1), glutathione (GSH), malondialdehyde (MDA) and total antioxidant capacity (TAC), and mRNA and protein expressions of SOD1, was investigated as confirmatory markers of oxidative stress induction. Cytotoxicity on cancerous MCF-7 and normal Vero cells were also evaluated using an MTT assay at 24 h post-injection. The injection of LPS induced a significant (p < 0.05) increase in SOD, GSH and TAC, whereas, the MDA was diminished. Hemolymph was collected from normal and treated larvae after 6, 12 and 24 h. The M. domestica superoxide dismutase (MdSOD1) transcripts were significantly (p < 0.05) upregulated 6 and 12 h post-treatment, while a significant downregulation was observed after 24 h. Western blot analysis showed that MdSOD1 was expressed in the hemolymph of the treated larvae with an increase of 1.2 folds at 6 and 12 h and 1.6 folds at 24 h relative to the control group. LPS-treated larval hemolymphs exhibited significant cytotoxicity with respect to the untreated ones against MCF-7 while Vero cells showed no cytotoxicity for both hemolymphs. The DPPH free radical scavenging activity was examined and a significant antioxidant potential potency was observed at 6 h (50% maximal inhibitory concentration (IC50): 63.3 ± 3.51 µg/mL) when compared to the control M. domestica larval hemolymph (IC50: 611.7 ± 10.41 µg/mL). Taken together, M. domestica larval hemolymph exhibited enhanced antioxidant and consequently increased cytotoxic capacities under stressed conditions.